“Menikah atau Tidak Menikah, itulah Pertanyaannya!” : Tinjauan Teologis terhadap Konsep Pribadi dan Pernikahan dalam Mengatasi Konsep Hidup Melajang di Indonesia - Harianja, Doni Herwanto (Verbum Christi: Jurnal Teologi Reformed Injili, 2024)
This article explores societal perspectives, particularly within Christian communities, on the concept of marriage, which has increasingly become marginalized due to societal priorities on education and career. This situation has led to more complex criteria and expectations for potential partners, where individuals are treated as consumable objects and are judged based on external standards, such as economic status and education. However, individuals can understand their personhood theologically and holistically through deep interactions, meaningful relationships, and mutual self-giving in interpersonal connections, as exemplified in marriage. The uniqueness of personhood is also realized through relating with another person. Through a theological reflection on the concepts of personhood and marriage, this article emphasizes the importance of marriage as a life calling that should not be a secondary option after career and educational achievements. This article concludes that the church should take an active role in addressing theological understandings of marriage and respond thoughtfully to the issue of singleness.